ACTR-35. MOLECULAR MATCHMAKING: EFFICACY OF EARLY CLINICAL TRIALS GUIDED BY NEXT-GENERATION SEQUENCING IN PATIENTS WITH GLIOBLASTOMA MULTIFORME. (5th November 2018) - Leary, Jacob; Pearlman, Michael; Falchook, Gerald
Abstract: INTRODUCTION: Next-generation sequencing (NGS) is available for analysis of tumors in patients with glioblastoma multiforme (GBM) and can be used to match patients to clinical trials of agents that target specific alterations. We studied the relationship between molecular matching by NGS and treatment outcome in GBM patients treated on trials of targeted agents. METHODS: Patients were adults with GBM who enrolled on clinical trials at our center. Patients underwent NGS with either FoundationOne (tissue) or Guardant360 (cell-free DNA) prior to enrollment on a trial. Treatment was classified as a direct match, indirect match, or non-match. Clinical benefit was defined as complete response, partial response, or at least 4 months on treatment without progressive disease by RANO criteria. RESULTS: 19 consecutive patients underwent NGS and were treated on 1 or more of 8 different clinical trials, including 4 patients who were treated on 2 trials, for a total of 23 cases analyzed. 10 patients were male; 9 were female. Median age was 58 years (range 26–73). Median number of prior systemic therapies was 1. Three cases were a direct match, 8 cases were an indirect match, and 12 cases were a non-match. Clinical benefit was observed in 54.5% of patients with a direct or indirect match vs. 8.3% of patients with a non-match. Mean treatment duration was 252 days for patients with a direct or indirect match vs. 57 days for patients with a non-match. CONCLUSION: GBM patients treated on clinical trials of targeted agents that were a direct match or indirect match had a trend of longer duration of treatment and higher rate of clinical benefit, compared to trials that were a non-match. These observations support the use of next-generation sequencing to identify clinical trials for patients with GBM.